1997
DOI: 10.1046/j.1365-3083.1997.d01-412.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tyrosine Kinase Enzymes in TNF‐α and IL‐1 Induced Expression of ICAM‐1 and VCAM‐1 on Human Umbilical Vein Endothelial Cells

Abstract: The aim of this study was to analyse the potential roles of protein kinase enzymes in tumour necrosis factor-a (TNF-a) and interleukin-1 (IL-1) induced expression of the adhesion molecules intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1) on human umbilical vein endothelial cells (HUVEC). The authors observed a marked increase in ICAM-1 and VCAM-1 expression on HUVEC stimulated for 24 h by TNF-a (10 ng/ml) or IL-1 (20 ng/ml). Pre-treatment of HUVEC for 30 min with protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…CBMCs do not produce any detectable IL-1␤ (Ͻ3.9 pg/ml) following antibody-enhanced dengue virus infection (data not shown). Previous reports have indicated that (20 ng/ml) IL-1␤ induces HUVEC upregulation (31). Importantly, these reported levels are at least 1,000 times higher than those produced by HMC-1 cells and CBMCs.…”
mentioning
confidence: 80%
“…CBMCs do not produce any detectable IL-1␤ (Ͻ3.9 pg/ml) following antibody-enhanced dengue virus infection (data not shown). Previous reports have indicated that (20 ng/ml) IL-1␤ induces HUVEC upregulation (31). Importantly, these reported levels are at least 1,000 times higher than those produced by HMC-1 cells and CBMCs.…”
mentioning
confidence: 80%
“…It was also demonstrated that genistein inhibits lipopolysaccharide-stimulated TNF-production in a macrophage cell line [104] and TNF-levels in vivo [105]. Genistein also dosedependently inhibits TNF--induced MCP-1, ICAM-1 ,VCAM-1 [106][107][108] and matrix metalloproteinases (MMPs) [109] secretion both in vitro and in vivo, and the proliferation of VSMCs from spontaneously hypertensive rats [110].…”
Section: Genistein and Vascular Inflammationmentioning
confidence: 99%
“…According to Collins et al [6], the strong positivity on stimulated HUVEC can be explained by induction of ICAM-1 gene expression by TNF·. For Majewska et al [46] the costimulatory effect of TNF-· in combination with protein tyrosine kinase inhibitors on ICAM-1 expression suggests an intracellular pathway of TNF-·-induced ICAM-1 expression, possibly involving downregulation of increases in ICAM-1 by protein tyrosine kinase enzyme.…”
mentioning
confidence: 99%